The concepts of asymmetric and symmetric power can help resolve the puzzle of altruistic and cooperative behaviour. (11th July 2017) - Phillips, Tim
ABSTRACT: Evolutionary theory predicts competition in nature yet altruistic and cooperative behaviour appears to reduce the ability to compete in order to help others compete better. This evolutionary puzzle is usually explained by kin selection where close relatives perform altruistic and cooperative acts to help each other and by reciprocity theory (i.e. direct, indirect and generalized reciprocity) among non‐kin. Here, it is proposed that the concepts of asymmetry and symmetry in power and dominance are critical if we are ever to resolve the puzzle of altruism and cooperation towards non‐kin. Asymmetry in power and dominance is likely to emerge under competition in nature as individuals strive to gain greater access to the scarce resources needed to survive and reproduce successfully. Yet asymmetric power presents serious problems for reciprocity theory in that a dominant individual faces a temptation to cheat in interactions with subordinates that is likely to far outweigh any individual selective benefits gained through reciprocal mechanisms. Furthermore, action taken by subordinates to deter non‐reciprocation by dominants is likely to prove prohibitively costly to their fitness, making successful enforcement of reciprocal mechanisms unlikely. It is also argued here that many apparently puzzling forms of cooperation observed in nature (e.g. cooperative breeding in which unrelated subordinates help dominants to breed) might be best explained by asymmetry in power and dominance. Once it is recognized that individuals in these cooperative interactions are subject to the constraints and opportunities imposed on them by asymmetric power then they can be seen as pursuing a 'least bad' strategy to promote individual fitness – one that is nevertheless consistent with evolutionary theory. The concept of symmetric power also provides important insights. It can inhibit reciprocal mechanisms in the sense that symmetric power makes it easier for a cheat to appropriate common resources while incurring fewer penalties. Nevertheless under certain restrictive conditions, symmetric power is seen as likely to promote direct reciprocity through 'tit for tat'.